(untitled) (Research, Society and Development, 2020)
One of the great challenges for dentistry students when they finish their undergraduate course is to enter the job market. The objective of this literature review, narrative, was to evaluate the possibilities of access to information on management, entrepreneurship and marketing for dentistry students. Articles published between 2000 and 2020, in English and Portuguese, were evaluated in the following databases: Pumed, Lilacs, Scielo, Cochrane Library, Scopus, Web of Science, Embase and Bireme. The results showed that all over the world we see a disparity in dental students in the administrative issue, where few congratulate the management, entrepreneurship and marketing tools. The profession of dentist allows acting in several spheres: private, public, academic, and in various sectors; unfortunately the undergraduate course does not cover these possibilities and the student does not know exactly what to do at the end of the course. Few dentistry professionals are really financially satisfied and in view of this fact, we can observe that student doubts such as non-entrepreneurial planning during college may be one of the causes. Adequacy of the curriculum is necessary so that the themes of management, entrepreneurship, professional guidance are part of the student’s education and can effectively assist and promote professional growth.